THE WONDERFUL WIZARD OF OZ - Baum, L. Frank, (Lyman Frank), 1856-1919 (New York : UNION SQUARE KIDS, 2024)
Come along, Toto, she said. We will go to the Emerald City and ask the Great Oz how to get back to Kansas again. Swept away from her home in Kansas by a tornado, Dorothy and her dog Toto find themselves stranded in the fantastical Land of Oz. As instructed by the Good Witch of the North and the Munchkins, Dorothy sets off on the yellow brick road to try and find her way to the Emerald City and the Wizard of Oz, who can help her get home. With her companions the Scarecrow, the Tin Woodman and the Cowardly Lion, Dorothy experiences an adventure full of friendship, magic and danger. A much-loved children's classic, The Wizard of Oz continues to delight readers young and old with its enchanting tale of witches, flying monkeys and silver shoes.
Keywords: Gale, Dorothy -- (Fictitious character), -- Juvenile fiction; Children's stories; Oz (Imaginary place) -- Juvenile fiction